(untitled) (Italian Journal of Public Health, 2004)
Public health observatories (PHOs) were created in England in 2000. Since then they have been engaged in a variety of activities to support the health improvement agenda in England. This article describes these activities, the key responsibilities and outputs of PHOs. It also describes the links with other observatories in Europe.